2015
DOI: 10.1002/brb3.400
|View full text |Cite
|
Sign up to set email alerts
|

Persistent astrocyte activation in the fragile X mouse cerebellum

Abstract: BackgroundFragile X Syndrome, the most common single gene cause of autism, results from loss of the RNA‐binding protein FMRP. Although FMRP is highly expressed in neurons, it has also recently been identified in glia. It has been postulated that in the absence of FMRP, abnormal function of non‐neuronal cells may contribute to the pathogenesis of the disorder. We previously demonstrated reduced numbers of oligodendrocyte precursor cells and delayed myelination in the cerebellum of fragile X (Fmr1) knockout mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 51 publications
(115 reference statements)
2
24
0
Order By: Relevance
“…Here, we observed that Fmr1 KO mice exhibited prominent GFAP expression, while in vitro astrocyte cultures displayed hypertrophy and increased GFAP levels, all of which are hallmark features of reactive astrogliosis. In support of our findings, separate studies have provided evidence for astrocytic activation in the cerebellum of Fmr1 KO mouse [66,67] and in patients with autism [65,72]. Zamanian et al conducted an extensive analysis on the genomic profile of reactive astrocytes, where they identified numerous genes of different signaling pathways were significantly induced [73].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Here, we observed that Fmr1 KO mice exhibited prominent GFAP expression, while in vitro astrocyte cultures displayed hypertrophy and increased GFAP levels, all of which are hallmark features of reactive astrogliosis. In support of our findings, separate studies have provided evidence for astrocytic activation in the cerebellum of Fmr1 KO mouse [66,67] and in patients with autism [65,72]. Zamanian et al conducted an extensive analysis on the genomic profile of reactive astrocytes, where they identified numerous genes of different signaling pathways were significantly induced [73].…”
Section: Discussionsupporting
confidence: 83%
“…With regards to FXS, microglia can directly mediate dendritic spine elimination via the complement system where excessive synapses are tagged with complement proteins (C1q and C3) and consequently engulfed by microglial cells expressing complement receptors [24,62,63]. There is clinical evidence suggesting excessive microglial activation in multiple brains regions of patients with ASD [64,65], but other studies did not detect any microglial activation or altered cytokine production in the Fmr1 KO mice [66,67]. In our study, we found a slight reduction in the number of Iba1-positive cells across the neocortex of Fmr1 KO mutants, further justifying the absence of microglial activation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found that the level of glial fibrillary acidic protein (GFAP) is increased at 4 weeks when FMRP is depleted. Increased astrocyte differentiation was also reported from adult neural stem cells and hESCs and GFAP is upregulated in human and mouse postnatal brain . As astrocytes are involved in the developing synapse and in the abnormal dendritic arbors of Fmr1 ‐KO mice , we suggest that the increase of GFAP during early steps of neurogenesis contribute to the neuronal alterations observed in FXS.…”
Section: Discussionsupporting
confidence: 63%
“…One group reports no astrogliosis seen in post-mortem brains of persons with FXS (41). On the other hand, an elevated number of activated astrocytes was observed in the cerebellum of Fmr1 KO mice (42). Our results show no gross changes in the volume or reactivity of cortical astrocytes, but we can not exclude subtle changes to the fine astrocyte processes or alterations in astrocytic signaling exist.…”
Section: Discussionmentioning
confidence: 99%